Evaluation of recombinant adenovirus vectors and adjuvanted protein as a heterologous prime-boost strategy using HER2 as a model antigen. Issue 47 (8th November 2019) - Haq, Kamran; Jia, Yimei; Elahi, S. Mehdy; MacLean, Susanne; Akache, Bassel; Gurnani, Komal; Chattopadhyay, Anindita; Nazemi-Moghaddam, Nazila; Gilbert, Rénald; McCluskie, Michael J.; Weeratna, Risini D.
Abstract: Induction of strong antigen-specific cell-mediated and humoral responses are critical to developing a successful therapeutic vaccine. Herein, using HER2 as a model antigen, we aim to evaluate a therapeutic vaccine protocol that elicits anti-tumor antibody and cytotoxic T cells to HER2/neu antigen. Replication-competent (ΔPS AdV) and non-replicating recombinant adenoviral vectors (AdV) expressing a rat HER2/ neu (ErbB2) oncogene, were generated and compared for four different doses and over four time points for their ability to induce antigen-specific T and B cell responses in mice. Although ΔPS AdV:Her2 vector was shown to induce more durable antigen-specific CD8 + T cell responses, overall, the AdV:Her2 vector induced broader T and B cell responses. Hence the AdV:Her2 vector was used to evaluate a heterologous prime-boost vaccination regimen using rat HER2 protein encapsulated in archaeosomes composed of a semi-synthetic glycolipid (sulfated S-lactosylarchaeol, SLA; and lactosylarchaeol, LA) (SLA/LA:HER2enc) or admixed with archaeosomes composed of SLA alone (SLA:HER2adm). We first tested AdV:Her2 using a prime-boost approach with SLA/LA:HER2enc, and thereafter evaluated a sub-optimal AdV:Her2 dose in a heterologous prime-boost approach with SLA:HER2adm. A single administration of AdV:Her2 alone induced strong cell-mediated immune responses, whereas SLA/LA:HER2enc alone induced strong antigen-specific IgG titers. In mice primed with a suboptimal dose of AdV:Her2, strong CD8 + T-cell responses were observed after a single dose which were not further augmented by protein boost. AdV:Her2 induced CD4 + specific T-cell responses were augmented by SLA:HER2adm. Homologous vaccination using SLA:HER2adm induced strong antigen-specific antibody responses. However, the overall magnitude of the responses was similar with three doses of SLA:HER2adm or Ad:HER2 prime followed by two doses of SLA:HER2adm. We demonstrate that AdV:Her2 is capable of inducing strong antigen-specific CD8 + T cell responses, even at a low dose, and that these responses can be broadened to include antigen-specific antibody responses by boosting with SLA adjuvanted proteins without compromising CD8 T cell responses elicited by AdV priming.